Gain of Spontaneous clpX Mutations Boosting Motility via Adaption to Environments in Escherichia coli - Li, Bingyu; Hou, Chaofan; Ju, Xian; Feng, Yong; Ye, Zhi-Qiang; Xiao, Yunzhu; Gu, Mingyao; Fu, Chunxiang; Wei, Chaoliang; You, Conghui (Frontiers in Bioengineering and Biotechnology, 2021)
Motility is finely regulated and is crucial to bacterial processes including colonization and biofilm formation. There is a trade-off between motility and growth in bacteria with molecular mechanisms not fully understood. Hyper-motile Escherichia coli could be isolated by evolving non-motile cells on soft agar plates. Most of the isolates carried mutations located upstream of the flhDC promoter region, which up-regulate the transcriptional expression of the master regulator of the flagellum biosynthesis, FlhDC. Here we identified that spontaneous mutations in clpX boosted the motility of E. coli largely, inducing several folds of changes in swimming speed. Among the mutations identified, we further elucidated the molecular mechanism underlying the ClpXV78F mutation on regulation of E. coli motility. We found that the V78F mutation affected ATP binding to ClpX, resulting into the inability of the mutated ClpXP protease to degrade FlhD as indicated by both structure modeling and in vitro protein degradation assays. Moreover, our proteomic data indicated that the ClpXV78F mutation elevated the stability of known ClpXP targets to various degrees with FlhD as one of the most affected. In addition, the specific tag at the C-terminus of FlhD being recognized for ClpXP degradation was identified. Finally, our transcriptome data characterized that the enhanced expression of the motility genes in the ClpXV78F mutations was intrinsically accompanied by the reduced expression of stress resistance genes relating to the reduced fitness of the hyper-motile strains. Similar pattern was observed for previously isolated hyper-motile E. coli strains showing high expression of flhDC at the transcriptional level. Hence, clpX appears to be a hot locus comparable to the upstream of flhDC promoter region evolved to boost bacterial motility and our finding provides insight into the reduced fitness of the hyper-motile bacteria.